Chemical Constituents and Antioxidant Activity of Melothria scabra Naudin Fruits - Harni Sartika Kamaruddin; Megawati Megawati; Nurliana Nurliana; Carla Wulandari Sabandar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The fruit of Melothria scabra Naudin is traditionally used by natives of South East Sulawesi and has economic values in the local markets. Nonetheless, little scientific information was gained from this plant to support its development for nutraceutical and pharmaceutical aspects. This study aimed to investigate the phytochemicals contained in the ethanol extract and organic fractions (methanol, ethyl acetate, and hexane) of the fruits using specific reagents and an LC-MS/MS analysis, as well as to evaluate their total phenolics, total flavonoids, and DPPH radical scavenging activity using a dot-blot staining and spectrophotometric assays. Results showed that the fruits of M. scabra contained alkaloids, tannins, flavonoids, terpenoids, and saponins. Six compounds were successfully identified from the ethanol extract of the fruits for the first time that is D-1-[(3-carboxypropyl)amino]-1-deoxyfructose (1), fructose-C3H5NO (2), valine (3), 1β, 3α, 9β-trihydroxyeudesma-5,11(13)-dien-12-oic acid (4), Cucurbitacin B-2-O-α-L-rhamnopyranosyl-β-D-glucopyranoside (5), and 2-heptyl-3-hydroxy-4(H)-quinolone (6). Total phenolics in the extract and organic fractions were in the range of 54.2 ± 2.4 to 259.1 ± 8.4 mg GAE/g, while total flavonoids were in the range of 1.6 ± 0.2 to 22.4 ± 0.2 mg QE/g. The ethanol extract and its organic fractions (methanol and ethyl acetate) were potent radical scavengers with SC50 values ranging from 20.7 to 37.5 µg/mL when compared with ascorbic acid, gallic acid, and quercetin (SC50 of 2.8 to 9.4 µg/mL). This study concludes that M. scabra fruits could be developed as a source of natural antioxidant agents for nutraceuticals and pharmaceuticals purposes.